PERKEMBANGAN BAHASA SISWA MI KAITANNYA DENGAN PROSES BELAJAR DAN PERSPEKTIF ISLAM - Sukma, Hafika Mauludia; Zulhidah, Zulhidah; Bakhtiar, Nurhasanah (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2022)
School-age children are at an integrated stage of development, organizing and integrating different developmental abilities to handle increasingly complex tasks. One of them is language development. Language development is basically an individual's ability to communicate with the environment. Communication is used to build relationships with others so that we feel part of the environment. This paper aims to understand the pattern of language development of MI MI students with the learning process and an Islamic perspective. This is a qualitative research obtained by library research, namely by tracing various journals related to the discussion of students' language development with the learning process and Islamic perspective. The data analysis technique uses the Miles and Huberman model, where there are three stages used to analyze the data in this, the first is data reduction, namely the collection and selection of data related to the language development of MI students with the learning process and Islamic perspective. Then display the data, which is to understand the data that has been selected. And finally draw conclusions. Language skills develop during school education. Students will be able to understand and interpret verbal, written and body language communication, as well as being able to understand and understand the people around them.Â